Tuning the Crystalline Phase Transition Temperature of 1T‐TaS2 via Surface Oxidation - Lilin Yang; Shihao Hu; Genyu Hu; Weikang Zhou; Yubo Zhang; Tianyu Dai; Yun Zhang; Jinfeng Zhang; Chen Liu; Jia‐Ou Wang; Jingsi Qiao; Zhilin Li; et al. (Advanced Materials Interfaces)
Abstract Owning various and unique properties, the crystalline phases of transition metal dichalcogenides (TMDs) and the introduced phase engineering have a range of potential applications in future devices. The phase transition temperature, corresponding to the stability of the atomic structural phase, is one of the key parameters in the phase engineering study. However, the reported method for tuning the transition temperature is always complicated and brings impurities, impairing the properties. Here, tuning the phase transition temperature via the surface oxidation of the octahedral phase (1T)‐TaS2 is reported. The surface characterization results reveal that the phase transition would originate from the sulfur surface sublimation and its induced doping. Then the Ta oxide layer, a surface cap, is fabricated using O2 plasma treatment, without affecting the 1T‐TaS2 under the surface. As revealed by the Raman results, the phase transition temperature of 1T‐TaS2 increase significantly, in contrast to the samples without oxidation. The work provides a facile and effective method to tune the phase of the TMDs, toward the fabrication of the nanostructure based on the phase engineering for future applications.